2001
DOI: 10.1093/ps/80.6.769
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cage Density and Prior Dietary Phosphorus Level on Phosphorus Requirement of Commercial Leghorns

Abstract: Two studies were conducted to determine whether cage density and prior dietary nonphytate P (NPP) level affect hens' P requirements. In Experiment 1, hens were housed at three cage densities (300, 400, and 600 cm2 or 46.5, 62.0, and 93.0 inches2/hen) and fed four levels of NPP (0.15, 0.25, 0.35, and 0.40%) for 6 wk to determine the effect of cage density on the P requirement. Egg production (EP), feed consumption (FC), egg weight (EW), and egg specific gravity (ESG) were measured to evaluate performance. Cage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
3
8
2
Order By: Relevance
“…Data of external egg quality i.e., egg weight, specific gravity, egg shape index, shell weight and shell percentage recorded insignificant differences among the experimental groups. These reports are also agree with Sohail et al, (2001) showed that there were no significant effects of the different densities on egg quality traits in chicken such as egg weight, specific gravity, shell weight, shell percent at 81 weeks of age. Results from quails stocked at 140 cm 2 /bird recorded significantly (P≤0.05) high values of shell thickness, followed by those stocked at170, 200 and 233cm 2 /bird respectively.…”
Section: Hormonal Assays and Immunological Responsesupporting
confidence: 91%
See 1 more Smart Citation
“…Data of external egg quality i.e., egg weight, specific gravity, egg shape index, shell weight and shell percentage recorded insignificant differences among the experimental groups. These reports are also agree with Sohail et al, (2001) showed that there were no significant effects of the different densities on egg quality traits in chicken such as egg weight, specific gravity, shell weight, shell percent at 81 weeks of age. Results from quails stocked at 140 cm 2 /bird recorded significantly (P≤0.05) high values of shell thickness, followed by those stocked at170, 200 and 233cm 2 /bird respectively.…”
Section: Hormonal Assays and Immunological Responsesupporting
confidence: 91%
“…The decrease of performance due to increasing stoking density may be a result of physiological stress Hester et al, (1996 a, b). In this regard, Roush and Cravener (1990), Carey and Kuo (1995), Hashemi and Pourreza (1998), Sohail et al, (2001) and Özbey et al, (2004) found that the increase of cage density resulted in a significant reduction in egg production and egg mass. Also Anderson et al, (1995) and Gharib et al, (2005) showed that increased bird cage density resulted in a significant decreased in egg mass.…”
Section: Resultsmentioning
confidence: 96%
“…Keshavarz (2000) fed layers with 0.30, 0.35, and 0.40% avP and did not detect any differences in P excretion or blood P content. These observations suggest the the lowest avP level used in the present study (0.25 %) did not cause any problems because this level is not much lower than the recommendations and because the higher feed intake resulted in higher P intake, differently from the findings of Sohail et al (2001).…”
Section: Blood and Feces Calcium And Phosphorus Concentrationscontrasting
confidence: 45%
“…This increase in egg production averaged 15.9 number decreasing the space allowance from 2 000 cm 2 to 500 cm 2 per hen. Decreasing egg production was shown to be attributable to the reduced feeding area per hen, cannibalism (Hester and Wilson, 1986;Craig and Milliken, 1989;Lee and Moss, 1995;Süto et al, 1997;Sohail et al, 2001;Onbasilar and Aksoy, 2005;Jalal et al, 2006;Nicol et al, 2006) and stocking density (Adams and Craig, 1985). Anderson et al (2004) found out that the reduced cage stocking in Hy-Line W36 and Dekalb XL commercial layer genotypes decreased hen-day egg production.…”
Section: Discussionmentioning
confidence: 99%